2010
DOI: 10.1111/j.1439-037x.2010.00433.x
|View full text |Cite
|
Sign up to set email alerts
|

Root System Size Influences Water‐Nutrient Uptake and Nitrate Leaching Potential in Wheat

Abstract: Environmental and economic considerations require the effective use of water and nutrients to elevate grain production in bread wheat (Triticum aestivum L.) with concomitant reduction in nitrate leaching to minimize contamination of underground water. We determined the effect of the root system on leaching fraction, leachate N concentration, and N, P and K uptake using bread wheat ‘Pavon 76’ and its three near‐isogenic translocation lines: Pavon 1RS.1AL, Pavon 1RS.1BL and Pavon 1RS.1DL. These genotypes were gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
57
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(69 citation statements)
references
References 45 publications
8
57
1
Order By: Relevance
“…To improve NUpE, it was found that cultivars with a larger root system resulted in higher N uptake and did not necessarily decrease grain yield (see, e.g., Ehdaie et al 2010;Andresen et al 2016). Andresen et al (2016) showed that among nine spring wheat cultivars in 2-m-deep tube rhizotrons, the total root biomass could differ almost twofold, and that also the spatial distribution of their root systems in the soil differed substantially.…”
Section: Winter Wheatmentioning
confidence: 99%
See 1 more Smart Citation
“…To improve NUpE, it was found that cultivars with a larger root system resulted in higher N uptake and did not necessarily decrease grain yield (see, e.g., Ehdaie et al 2010;Andresen et al 2016). Andresen et al (2016) showed that among nine spring wheat cultivars in 2-m-deep tube rhizotrons, the total root biomass could differ almost twofold, and that also the spatial distribution of their root systems in the soil differed substantially.…”
Section: Winter Wheatmentioning
confidence: 99%
“…This leads to the statement that the uptake of cabbage is already quite efficient (ThorupKristensen 2006a;Schulte auf'm Erley et al 2010); however, research to date has only focused on a limited set of cultivars and to the best of our knowledge, no research has included a large set of genotypes to show whether there is variation that can be exploited in breeding to improve uptake efficiency in cabbage. Moreover, wheat can also root to the same depth as cabbage (2.0 m) and for wheat, much variation has been shown for N uptake and for root length densities at larger depth (beyond 1 m) (Ehdaie et al 2010;Andresen et al 2016). Interestingly, Schulte auf 'm Erley et al (2010) found that N uptake under high N showed more variation whereas under low N, no variation was found.…”
Section: Nitrogen Uptake Efficiencymentioning
confidence: 99%
“…Total root length density and root biomass (Waines and Ehdaie 2007;Ehdaie et al 2010) are indicators of the size of a root system. A vigorous root system which has large biomass, length and root length density is then considered as a large root system.…”
Section: Invigorating the Root System In Wheat Is Increasing Its Sizementioning
confidence: 99%
“…In reduced-input agricultural systems, root traits affecting the acquisition of mineral elements often determine yield (Ehdaie et al 2010;White et al 2013). In the Mediterranean Basin, one of the largest durum wheat producers in the world, more than 50 % of the total grain of durum wheat is produced in arid and semi-arid conditions, with severe drought most years (Loss and Siddique 1994;Araus et al 2003;García del Moral et al 2005).…”
Section: Introductionmentioning
confidence: 99%